TRANSTHORACIC PUNCTURE BIOPSY IN DIAGNOSTICS OF FOCAL LESIONS OF THE LUNG - E. A. Drobyazgin; A. S. Kudryavtsev; Yu. V. Chikinev; A. A. Zheravin; E. M. Blagitko; S. G. Shtofin; O. A. Shumkov (Вестник хирургии имени И.И. Грекова)
The transthoracic puncture biopsy was performed under surveillance of X-ray computed tomography in order to verify diagnoses in 80 patients with lung tumors. This procedure allowed verification of diagnosis and choice of treatment strategy in 95% of cases. The complications obtained as result of intervention didn’t bring severe character and were arrested in term of two days.